Pengaruh Bimbingan Mental Spiritual Terhadap Regulasi Emosi Remaja - Syamsiah, Rita Elly; Kusnawan, Aep; Saepulrohim, Asep (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This study aims to determine how much influence mental spiritual guidance has on adolescent emotional regulation. Subjects in this study were 60 students. The method used in this research is a survey method. The regression data analysis technique refers to the Pearson rank formula. The results of data analysis showed that spiritual mental guidance had an effect on emotional regulation with statistically significant values (r = 0.35, p = 0.007 <0.05) and KD results = 12.39%, which means that there is an influence of spiritual mental guidance on adolescent emotional regulation. female students at the Nurul Iman Islamic Boarding School Cisalak, Subang City by 12.39%. While the rest of the percentage is influenced by other factors.